2018
DOI: 10.3389/fnins.2018.00807
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Brain Monosynaptic Afferent Projections to the Cholecystokinin Neurons of the Suprachiasmatic Nucleus

Abstract: The suprachiasmatic nucleus (SCN) is the principal pacemaker driving the circadian rhythms of physiological behaviors. The SCN consists of distinct neurons expressing neuropeptides, including arginine vasopressin (AVP), vasoactive intestinal polypeptide (VIP), gastrin-releasing peptide (GRP), cholecystokinin (CCK), and so on. AVP, VIP, and GRP neurons receive light stimulation from the retina to synchronize endogenous circadian clocks with the solar day, whereas CCK neurons are not directly innervated by retin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 67 publications
0
26
0
Order By: Relevance
“…To this end, we also noted substantial input from several preoptic cell groups, suggesting a potential circuit substrate by which temperature sensitive neurons might modulate, and possibly entrain, SCN VIP neurons 56 . It is also useful to contrast our findings with those from a recent rabies-based tracing study 57 which showed that CCK-expressing SCN neurons, which are generally intermingled with, but are also distinct from, SCN VIP neurons, receive input from a large number of hypothalamic and preoptic structures, but not from the retina, and minimally from the IGL.…”
Section: Discussionmentioning
confidence: 78%
“…To this end, we also noted substantial input from several preoptic cell groups, suggesting a potential circuit substrate by which temperature sensitive neurons might modulate, and possibly entrain, SCN VIP neurons 56 . It is also useful to contrast our findings with those from a recent rabies-based tracing study 57 which showed that CCK-expressing SCN neurons, which are generally intermingled with, but are also distinct from, SCN VIP neurons, receive input from a large number of hypothalamic and preoptic structures, but not from the retina, and minimally from the IGL.…”
Section: Discussionmentioning
confidence: 78%
“…AAV2/9-CAG-DIO-TVA-GFP (1.7 9 10 13 genome copies/mL), AAV2/9-CAG-DIO-RG (6.8 9 10 12 genome copies/mL), and an EnvA-pseudotyped glycoprotein (RG)deleted and DsRed-expressing rabies virus (RV-EnvA-DG-DsRed, 5.0 9 10 8 fluorescence-forming units/mL) were purchased from BrainVTA (Wuhan, China) [21,22]. The two Cre-dependent AAVs were mixed at a 1:1 ratio in 100 nL as helper viruses for retrograde monosynaptic-tracing experiments.…”
Section: Viruses and Surgerymentioning
confidence: 99%
“…Surgical procedures were performed as described in previous studies [22,23]. Briefly, mice were anesthetized with chloral hydrate (350 mg/kg, intraperitoneal) and placed in a stereotaxic apparatus.…”
Section: Viruses and Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Input to the SCN also arises from hypothalamic and brain stem areas, including the PVH and the preoptic area (Pickard 1982;Yuan et al 2018), although the functional relevance of most such bidirectional circuits remains largely unknown. Serotonergic input from the brain stem raphe nuclei is particularly dense to the SCN (Meyer-Bernstein and Morin 1996; Pickard and Rea 1997) and may be involved in modulating functions such as how light and locomotor activity rhythms convey entrainment signals to the SCN Marchant et al 1997).…”
Section: Circadian Neurocircuitry Regulating Appetite Sleep and Enementioning
confidence: 99%